2002
DOI: 10.1523/jneurosci.22-06-02265.2002
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Cholinergic Amacrine Cells by a Novel Immunotoxin Does Not Perturb the Formation of Segregated On and Off Cone Bipolar Cell Projections

Abstract: Cone bipolar cells are the first retinal neurons that respond in a differential manner to light onset and offset. In the mature retina, the terminal arbors of On and Off cone bipolar cells terminate in different sublaminas of the inner plexiform layer (IPL) where they form synapses with the dendrites of On and Off retinal ganglion cells and with the stratified processes of cholinergic amacrine cells. Here we first show that cholinergic processes within the On and Off sublaminas of the IPL are present early in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 72 publications
3
25
0
Order By: Relevance
“…The pattern and level of stratification of the axonal arbors of bipolar cells in the inner plexiform layer, which reflect their functional diversity, are not influenced by major changes in retinal architecture: the neonatal elimination of ganglion cells, which are their major target (Gunhan-Agar et al, 2000), the selective removal of cholinergic amacrine cells (Gunhan et al, 2002), the formation of supernumerary neurons in the inner nuclear layer (Strettoi and Volpini, 2002), or an imbalance in afferent activity (Bodnarenko et al, 1995), do affect the number of bipolar cells but not the connectivity in the ipl. Our data demonstrate that the lamination of rod bipolar cells, and probably the wiring of their axons, are not affected by the absence of their normal presynaptic partners.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern and level of stratification of the axonal arbors of bipolar cells in the inner plexiform layer, which reflect their functional diversity, are not influenced by major changes in retinal architecture: the neonatal elimination of ganglion cells, which are their major target (Gunhan-Agar et al, 2000), the selective removal of cholinergic amacrine cells (Gunhan et al, 2002), the formation of supernumerary neurons in the inner nuclear layer (Strettoi and Volpini, 2002), or an imbalance in afferent activity (Bodnarenko et al, 1995), do affect the number of bipolar cells but not the connectivity in the ipl. Our data demonstrate that the lamination of rod bipolar cells, and probably the wiring of their axons, are not affected by the absence of their normal presynaptic partners.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in rats has also demonstrated that bipolar cell stratification is normal in the absence of RGCs (Gunhan-Agar et al, 2000). In addition, in rats treated with an immunotoxin that selectively eliminates starburst amacrine cells, bipolar cell stratification appears normal (Gunhan et al, 2002) [ Fig. 3(B)].…”
Section: Role Of Nachr-mediated Waves In Retina Developmentmentioning
confidence: 95%
“…Normal P12 retina is shown on left P12 retina where cholinergic cells were depleted at P2 is shown on right. (Adapted from Gunhan et al, 2002). Muir-Robinson et al, 2002).…”
Section: Role Of Nachr-mediated Waves In Retinogeniculate Developmentmentioning
confidence: 99%
“…With no absolute requirement for their major synaptic partners, how do amacrine cells achieve their stratification pattern? This question has remained elusive, as available immunocytochemical markers only label differentiated amacrine cells after they are stratified (Bansal et al, 2000;Gunhan et al, 2002;Reese et al, 2001;Stacy and Wong, 2003). It has therefore not been possible to determine whether amacrine cell neurites remodel within the IPL before occupying a sublamina, or whether they specifically target a sublamina, responding to cues already present in the nascent IPL.…”
mentioning
confidence: 99%